Surface inspection problems in thermoelectric testing; MATEC Web of Conferences; Vol. 102 : Space Engineering - Abouellail A. A. S. A. R. Ahmed Ali Sabri Ahmed Refaat; Obach I. Igor; Soldatov A. A. Andrey Alekseevich; Soldatov A. I. Aleksey Ivanovich (2017, 2017)
Title screen